Kegiatan Pengmas Penyuluhan Problem Solving Klaim BPJS di RS - Sri Wahyuni Sambo (Natural: Jurnal Pelaksanaan Pengabdian Bergerak bersama Masyarakat., 2024)
The ongoing health problems in Indonesia require the government to take action so that people can still experience justice and obtain their rights and not cause harm. In order to improve the quality of public health, the government provides social security. This social security is provided by the government and is useful for meeting the basic needs of a decent life, starting from Jamkesmas, Jamkesda, AKSES and most recently the Social Security Administering Body (BPJS) for Health. Even though there have been efforts by the government to realize efforts to resolve existing problems, these efforts have not been effective due to several inhibiting factors. A solution is needed in the form of establishing and implementing the IMP (Identity Monitoring Program) concept which is integrated with the Capil Population and Civil Registry Department and BPJS. It is hoped that the application of the IMP concept can minimize the deficit in health insurance and become a solution to solving claims management problems as one of the root causes of the BPJS deficit.